Analisis Yuridis Perceraian Perkawinan Campuran Akibat Kekerasan yang Dilakukan oleh Pihak Istri Ditinjau dari Peraturan Perundang-Undangan Terkait - Salsabila Putri Nadira; Djanuardi Djanuardi; Betty Rubiati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Mixed marriages between Indonesian citizens (WNI) and foreign nationals (WNA) often give rise to legal issues, particularly in divorce cases involving the division of marital property. A key challenge arises from the restriction on land ownership for foreign nationals under the Basic Agrarian Law. This study examines Decision Number 146/Pdt.G/2021/PA.Dps, in which an Indonesian wife was accused of extortion against her foreign husband in the context of a mixed marriage divorce. Using a normative juridical method and a descriptive-analytical approach, the study finds that the wife’s act of withholding her husband’s documents does not constitute extortion, but rather a form of self-protection due to the husband's failure to provide financial support. The findings emphasize that the division of marital assets in mixed marriages must consider the provisions of the Marriage Law, the Compilation of Islamic Law for Muslim couples, and the Basic Agrarian Law, especially regarding land ownership by foreign nationals. Therefore, resolving property disputes in mixed marriages requires a careful legal approach to ensure compliance with applicable laws.